Chlorophyll content measurement of drought tolerant wheat genotypes sown at normal and late conditions as an indicator of spot blotch resistance - Aryal, L.; Shrestha, S. M.; Khatri-Chhetri, G. B.; Bhandari, D. (Journal of the Institute of Agriculture and Animal Science, 2018)
A field experiment was conducted at Agronomy block of the Institute of Agriculture and Animal Science (IAAS), Rampur to evaluate chlorophyll content of 20 drought tolerant wheat genotypes as a parameter of stay green character and spot blotch response. The experiment was laid out in a split plot design with three replications, considering 25 November as normal sowing and 15 December as late sowing dates. Of the tested genotypes, Aditya had highest SPAD value (46.67) with least AUDPC (146) on flag leaf on 25 November sowing and higher SPAD value (43.57) with lower AUDPC (161) on 15 December sowing. Similarly, CSISA DRYT 5204 and CSISA DRYT 5205 had moderate SPAD values with AUDPC value at par with Aditya. Aditya with low AUDPC possessed longer stay green days (118.3) on 25 November sowing and shorter green days (107.5) on 15 December sowing. The susceptible check variety RR-21 possessed shorter stay green days (113.6) with SPAD value (35.7) on 25 November sowing and 100.4 days of stay green with SPAD value (31.23) on 15 December sowing. Aditya also had highest grain yields and thousand kernel weights on both the 25 November and 15 December sowing. The results showed Aditya, CSISA DRYT 5204 and CSISA DYRT 5205 were having longer period of stay green with higher SPAD and low AUDPC values and thus these three genotypes can be recommended for late sown conditions. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 65-72